68=m-46

Simple and best practice solution for 68=m-46 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 68=m-46 equation:


68=m-46

We simplify the equation to the form, which is simple to understand
68=m-46

We move all terms containing m to the left and all other terms to the right.
-1m=-46-68

We simplify left and right side of the equation.
-1m=-114

We divide both sides of the equation by -01 to get m.
m=114

See similar equations:

| x+7overx-5=0 | | f(x)=-x^2+1.8x+14.4 | | 2(4-x)=x | | -2x-4x-12=6 | | 3j+-2j-11=7 | | -8x+2y=-6 | | -x-2x-7x-2=32 | | n^2+12n-49=-10 | | 5(2+x)=7x-20 | | (15x-9)=y | | 2x(2-x)=x | | 9n-32=24n-1 | | 0.32/0.56=8/x | | 8-8b=8(b-7) | | N+4-3=2 | | f(x)=-2x^2+4x-1 | | -4(5t-4)+7t=5t-7 | | 9(x-4)=37 | | 6(x-.333)=-2(x+23) | | 540-3x=360-2x | | 14x-(x-5)+8=13 | | 320=0.2(1.500+x) | | -(7-4k)=9 | | .9x+8.25=1.5(2+2x) | | 3y=-6x-21 | | -15+5=-2(x+7) | | 6(x-3)+2x=4(2x-1)-22 | | 2(y+7)-7y=-16 | | -2(3t-5)+4t=7t-9 | | (8x^9)^2/3 | | 43+7x= | | 62.1=20+0.5x+0.15(20+0.5x) |

Equations solver categories